Diversity and Composition of Termites in Several Types of Land Use - Heriza, Sri; Buchori, Damayanti; Harahap, Idham Sakti; Maryana, Nina (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Changes in land use due to deforestation can affect the diversity, composition, and structure of fauna communities, including termites. This study aims to examine the diversity, composition, and structure of the termite community in several land uses. Land uses include natural forest, secondary forest, plantation of oil palm, and settlements in Dharmasraya District, West Sumatra Province. The research was conducted to determine the distribution of species and termite colonies in Dharmasraya District. The research method used observation on the level of habitat disturbance. The observations were conducted on 50 m x 10 m plots. One plot was split into 5 m x 5 m sub-plots, and there were 20 sub-plots in total. Termite samples collected from each plot were identified in the laboratory. This study found 14 species of termites on different land uses in Dharmasraya Regency West Sumatra Province. The level of disturbance of land use types affects the composition and structure of termites within it, especially from taxon groups and their food groups, and there are similarities in termite species composition in natural forests and secondary forests and and also similarities on termite species composition in oil palm plantations and settlements.